2016
DOI: 10.1002/psc.2860
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide (Cn-AMP2) from liquid endosperm ofCocos nuciferaforms amyloid-like fibrillar structure

Abstract: Cn-AMP2 is an antimicrobial peptide derived from liquid endosperm of coconut (Cocos nucifera). It consists of 11 amino acid residues and predicted to have high propensity for β-sheet formation that disposes this peptide to be amyloidogenic. In the present study, we have examined the amyloidogenic propensities of Cn-AMP2 in silico and then tested the predictions under in vitro conditions. The in silico study revealed that the peptide possesses high amyloidogenic propensity comparable with Aβ. Upon solubilisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…In past years, several studies have reported the self‐assembly phenomenon of AMPs . Our group has previously reported the formation of amyloid‐like assemblies by a plant AMP . Interestingly, it is furthermore reported that some amyloids possess antimicrobial activity in vivo, eg, Aβ and hIAPP have the antimicrobial properties as part of their biological function .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In past years, several studies have reported the self‐assembly phenomenon of AMPs . Our group has previously reported the formation of amyloid‐like assemblies by a plant AMP . Interestingly, it is furthermore reported that some amyloids possess antimicrobial activity in vivo, eg, Aβ and hIAPP have the antimicrobial properties as part of their biological function .…”
Section: Introductionmentioning
confidence: 97%
“…[21][22][23][24][25][26] Our group has previously reported the formation of amyloid-like assemblies by a plant AMP. 27 Interestingly, it is furthermore reported that some amyloids possess antimicrobial activity in vivo, eg, Aβ and hIAPP have the antimicrobial properties as part of their biological function. [28][29][30] Other studies also provide information about antimicrobial activity associated with amyloid structures.…”
Section: Introductionmentioning
confidence: 99%
“…One should note that many amyloids in mammals are toxic and linked to disease [111]. Additionnaly, Shalini Gour et al recently demonstrated that a short antimicrobial peptide from the liquid endosperm of coconut (Cocos nucifera, Cn-AMP2, 11 amino acids: TESYFVFSVGN) can also autoassemble and fold into amyloid fibrils [112].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Among peptide elicitors, we chose PIP-1 (YGIHTH-NH 2 ), identified through combinatorial 65 chemistry, and Pep-13 (VWNQPVRGFKVYE-OH), a pathogen-associated molecular pattern (PAMP) from Phytophthora sojae, which trigger multiple defense responses in plant cells [24][25][26][27][28]. The promiscuous peptides studied were the AMPs Cn-AMP1 (SVAGRAQGM-NH 2 ), Cn-AMP2 (TESYFVFSVGM-NH 2 ) and Cn-AMP3 (YCSYTMEA-NH 2 ) identified from green coconut (Cocos nucifera) water [29,30]. 70…”
Section: Introductionmentioning
confidence: 99%
“…Realizing this need, we selected sequences described in the literature as plant defense elicitors, promiscuous, multifunctional or antimicrobial to be further tested against our target plant pathogens.Among peptide elicitors, we chose PIP-1 (YGIHTH-NH 2 ), identified through combinatorial 65 chemistry, and Pep-13 (VWNQPVRGFKVYE-OH), a pathogen-associated molecular pattern (PAMP) from Phytophthora sojae, which trigger multiple defense responses in plant cells [24][25][26][27][28]. The promiscuous peptides studied were the AMPs Cn-AMP1 (SVAGRAQGM-NH 2 ), Cn-AMP2 (TESYFVFSVGM-NH 2 ) and Cn-AMP3 (YCSYTMEA-NH 2 ) identified from green coconut (Cocos nucifera) water [29,30]. 70Regarding multifunctional peptides, we considered QKALNEINQF-NH 2 (p10) and TKKTKLTEEEKNRL-NH 2 (p14) which were isolated from bovine milk [31,32]; temporin-1CEa (FVDLKKIANIINSIFGK-NH 2 ), identified from the skin secretions of the Chinese brown frog (Rana chensinensis) [33-34]; the lactoferrin-derived peptide WFRKQLKW-OH (L10) [35]; frenatin 2.1S(GLVGTLLGHIGKAILG-NH 2 ) and frenatin 2.2S (GLVGTLLGHIGKAILS-NH 2 ) which were isolated 75 from skin secretions of the frog Sphaenorhynchus lacteus [36,37].…”
mentioning
confidence: 99%